Web-Based GIS for Oil Palm Land Suitability Assessment Using MAUT in Mandailing Natal Regency - Nanda Sitti Nurfebruary; Taufik Yunan Simamora; Fidyatun Nisa; Muhammad Ikhwani (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Land suitability assessment plays a critical role in plantation development planning, particularly for oil palm cultivation, which requires specific environmental conditions for optimal growth. Mandailing Natal Regency, a region with significant agricultural potential, necessitates a scientific approach to identify suitable areas for oil palm development. This study aims to develop a web-based Geographic Information System (GIS) integrated with the Multi-Attribute Utility Theory (MAUT) method to evaluate and map land suitability. The analysis utilizes both spatial and attribute data based on six key criteria: soil texture, rainfall, drainage, land slope, temperature, and soil pH. Each criterion is weighted according to its relative importance, and the MAUT method is applied to compute the overall utility value for each sub-district. The results are then visualized through an interactive GIS platform developed using the CodeIgniter framework. The system classifies land into four suitability categories: highly suitable (S1), moderately suitable (S2), marginally suitable (S3), and not suitable (N). The findings indicate that a substantial portion of the study area falls within the suitable and highly suitable categories, demonstrating strong potential for oil palm cultivation. This study provides a robust, data-driven tool to support decision-making in sustainable plantation development and improve land-use efficiency in Mandailing Natal Regency.